MEASURING Psychological Entitlement of the employees - Abbas Ali, Roaa; Raheem Ali, Abdul Halim (Al-Adab Journal, 2021)
The current study aims at measuring Psychological Entitlement among employees, and the differences in psychological entitlement among employees are identified according to the gender variable (male - female) and job status (contract - permanent), age (30 or less - more than 30) years. research sample is: 400 employees from the state ministries in Baghdad province following the stratified random method the psychological Entitlement scale is built, then the psychometric properties of the two measures were extracted. The research output: The employees have a low entitlement and statistically significant, and there are statistically significant differences in psychological entitlement accrual according to the variables (gender, job status, age).